Mixed Psychological Changes Following Mastectomy: Unique Predictors and Heterogeneity of Post-traumatic Growth and Post-traumatic Depreciation - Kroemeke, Aleksandra; Bargiel-Matusiewicz, Kamilla; Kalamarz, Magdalena (Frontiers in Psychology, 2017)
Objectives: Post-traumatic growth (PTG) and its opposite—post-traumatic depreciation (PTD)—may be treated as important indicators of the patient quality of life. In the absence of studies on both, PTG and PTD in cancer patients, we investigated (1) coping strategies and support effectiveness as predictors of PTG and PTD in post-mastectomy women, (2) homogeneous classes with different intensity of PTG and PTD symptoms, and (3) correlates of class membership. Methods: Coping strategies (Brief COPE), support effectiveness (SSE-Q), PTG (PTGI), and PTD (negatively reworded items of PTGI) were measured in 84 post-mastectomy women (mean age = 62.27, SD = 8.38). Multiple regression, two-step cluster, and multinomial logistic regression were applied. Results: PTG and PTD had unique predictors: time since diagnosis and positive emotion-focused coping predicted PTG (R2=.24), while negative emotion-focused and avoidance-focused coping and low support effectiveness were linked to PTD (R2=.14). Four groups of PTG × PTD symptoms were identified: high PTG low PTD group (52.4%), low PTG low PTD group (17.9%), high PTG high PTD group (15.5%), and low PTG high PTD group (14.3%). Higher emotion- and avoidance-focused coping was characteristic for the high PTD low PTG group (R2=.41). Conclusions: Our findings shed light on the coexistence and unique predictors of PTG and PTD after mastectomy, indicating heterogeneity in PTG and PTD levels among post-mastectomy women.